The Impact of Uncertainty on the European Energy Market: A Scenario Aggregation Approach - Kjell Arne Brekke; Rolf Golombek; Michal Kaut; Sverre A.C. Kittelsen; Stein W. Wallace (Center for Economic Studies and ifo Institute (CESifo), 2013)
We present a simple approach to transform a deterministic numerical model, where several agents simultaneously make decisions, into a stochastic model. This approach, which builds on scenario aggregation, a numerical method developed to solve decision problems under uncertainty, is used to build a large stochastic numerical equilibrium model of the Western European energy markets. We use the stochastic model to analyze the impact of economic and political uncertainty on the Western European energy markets. We demonstrate that the equilibria under uncertainty differ significantly from the deterministic outcomes.
Keywords: C63; C68; D58; D81; Q28; Q40; Q54; 330